2020
DOI: 10.3390/w12123467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tubificid Bioturbation on Vertical Water Exchange across the Sediment–Water Interface

Abstract: The bioturbation activity of macroinvertebrates can affect the level of water exchange across the sediment–water interface. The impact of tubificid worm with different densities on the vertical water exchange at the sediment–water interface was investigated based on laboratory flume experiments. Vertical water fluxes, as well as physiochemical parameters, were measured at seven-day intervals, and the maximum penetration depths were obtained by dye injection before and after the tubificid bioturbation experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Such findings are consistent with what is expected of L. variegatus , an upward conveyor bioturbator type that feeds head down (McCall & Fisher, 1980; Mermillod‐Blondin & Rosenberg, 2006; Nogaro et al, 2006). The ratio volume/area occupied by galleries was extensive and provided the basis to assume a potential increase in sediment permeability via increased porosity, which is particularly important to help offset the effects of streambed clogging (Mao et al, 2020). Roche et al, 2016 showed that the burrows were biased to the top 0.01 m of the bed, leaving large areas of the subsurface unaltered, with very rare activity in the deeper sections of the core.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are consistent with what is expected of L. variegatus , an upward conveyor bioturbator type that feeds head down (McCall & Fisher, 1980; Mermillod‐Blondin & Rosenberg, 2006; Nogaro et al, 2006). The ratio volume/area occupied by galleries was extensive and provided the basis to assume a potential increase in sediment permeability via increased porosity, which is particularly important to help offset the effects of streambed clogging (Mao et al, 2020). Roche et al, 2016 showed that the burrows were biased to the top 0.01 m of the bed, leaving large areas of the subsurface unaltered, with very rare activity in the deeper sections of the core.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exploring the ecological habitat of the Wei River, we also tried to investigate the close relationship between bioturbation and the external environment (e.g., hydrological variables, fine sediment, etc.). For example, is the macroinvertebrate bioturbation more intense in the clogged environment as in the artificial simulations (Mao et al, 2020)? Specific objectives of the paper are to (i) describe the assemblage characteristics of hyporheic macroinvertebrates across the Weihe River and assess the variations associated with fine sediments and seasons, (ii) examine the variability of bioturbation and its close relationship with environmental variables, and (iii) explain the interaction between macroinvertebrates and fine-sediment clogging.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies approached the stream and river systems from a variety of perspectives, ranging from the physical modelling of flow with vegetation [13] and the numerical simulation of solute transport in river with dead zones [14], to the laboratory study of flood discharge atomisation [15] and the geomorphic characterisation and classification of a large river [16]. Three contributions are about hyporheic fluxes: two field studies investigated these fluxes at a small river confluence [17] and the effects of such fluxes on the macroinvertebrate community [18], while their relationship with the bioturbation activity of macroinvertebrates was studied in laboratory [19]. The last two articles addressed the accuracy of groundwater flux measurement using a seepage meter in the laboratory [20] and the experimental validation of the Darcy-Buckingham (DB) law in unsaturated porous rocks [21].…”
mentioning
confidence: 99%
“…At the same time, the bioturbation activity of macroinvertebrates can affect the water exchange across the sediment-water interface (SWI) in the hyporheic zone. Mao et al [19] studied the impact of tubificid worms as a dominant group of benthic macroinvertebrates on the vertical water exchange across the sediment-water interface through laboratory flume experiments. The results showed that tubificid bioturbation affected the vertical water flux and penetration depth across the SWI, and such effects had pronounced correlation with both density and duration of bioturbation.…”
mentioning
confidence: 99%